Pelatihan Kompetensi Guru dalam Menggunakan Media Teknologi Informasi di SDIT Darul Hikmah Pekanbaru - Jailani, Ali Muddin (Bedelau: Journal of Education and Learning, 2023)
The use of information technology media in learning is an important factor in improving teaching effectiveness in the digital era, but many teachers still have difficulties in integrating technology due to limited skills and understanding. This study aims to analyze the effectiveness of teacher competency training in using information technology media at SDIT Darul Hikmah Pekanbaru using observation and interview methods. Observations were conducted to assess changes in the use of technology before and after training, while interviews explored teachers' experiences, constraints, and expectations. The results showed that after the training, teachers are more skilled in using digital platforms such as Google Classroom, Canva, and interactive PowerPoint, as well as applying more interactive learning methods. However, there are still obstacles such as limited technological devices and unstable internet access. In conclusion, this training has a positive impact on improving teachers' competence in utilizing technology, but it needs continuous support from schools in the form of providing adequate facilities and further training so that the use of technology in learning is more optimal.